Improving Public Understanding about Chronic Hepatitis and Diabetes Mellitus in The Era of The Covid-19 Pandemic - Effendy Effendy; Agus Aan Adriansyah; Akas Yekti Pulih Asih; Budhi Setianto; Evy Afifah Syagran; Iqbal Firdaus; Nikmatus Sa’adah (Universitas Andi Djemma, 2023)
Hepatitis is an inflammation of the liver. In chronic hepatitis, inflammation of the heart lasts for at least 6 months. Several incidences of disease in hepatitis require good and simultaneous treatment. To increase public knowledge regarding hepatitis, a webinar was held